2017
DOI: 10.5897/jmpr2017.6356
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical value of medicinal plant diversity in Cheha district, Guraghe zone, Southern Nations, Nationalities and Peoples (SNNPR) of Ethiopia

Abstract: This study aimed to document information on the use, conservation and threats to medicinal plants in Cheha district, Guraghe Zone, Southern Ethiopia. Thirty informants were randomly selected from four kebeles. Of which, 10 key informants were selected purposively by criteria of age, gender and indigenous knowledge. Ethnobotanical data was collected through semi-structured interview, guided field observation and group discussion. Data was analyzed with descriptive statistics and expressed with frequency distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
0
17
1
Order By: Relevance
“…The higher proportion of shrubs in this study will be associated with the demographic condition of the study area suitable for shrubs and the society engagement towards shrubs. This study was also found to be different from other studies [15,16,17,18] where herbs occupy the highest proportion. The reason why herbs are being investigated by many researchers as widely utilized is the use of herbaceous medicines seems valuable since they can replace themselves easily and they are ubiquitously easily accessible given a reasonable climatic condition.…”
Section: Medicinal Plant Distributioncontrasting
confidence: 99%
“…The higher proportion of shrubs in this study will be associated with the demographic condition of the study area suitable for shrubs and the society engagement towards shrubs. This study was also found to be different from other studies [15,16,17,18] where herbs occupy the highest proportion. The reason why herbs are being investigated by many researchers as widely utilized is the use of herbaceous medicines seems valuable since they can replace themselves easily and they are ubiquitously easily accessible given a reasonable climatic condition.…”
Section: Medicinal Plant Distributioncontrasting
confidence: 99%
“…The majority of medicinal plants used in Amaro (Mesfin et al, 2014), Bench (Giday et al, 2009), Cheha (Bizuayehu and Assefa, 2017), Dawro (Andarge et al, 2015), Kembatta (Maryo et al, 2015), South Omo (Tolossa et al, 2013), Mirab-Badwacho (Temam and Dillo, 2016) and Lowlands of Konta (Bekalo et al, 2009) areas of SNNPR are herbs (see Figure 1A). The high use of herbs as medicinal plants as compared to the other growth forms in these areas can be due their better abundance (availability) (Giday et al, 2009;Andarge et al, 2015).…”
Section: Growth Formsmentioning
confidence: 99%
“…The trend of using more of herbaceous plants in most areas SNNPR can be seen as a benefit because it is easier to cultivate herbs when they are in short supply and availability of more herbaceous plant species as compared to trees (Bekalo et al, 2009). (Mesfin et al, 2014;Giday et al, 2009;Bizuayehu and Assefa, 2017;Andarge et al, 2015;Maryo et al, 2015;Tolossa et al, 2013;Mesfin et al, 2009;Temam and Dillo, 2016;Kebebew and Mohamed, 2017;Bekalo et al, 2009), (B) Proportion of medicinal plants used to treat human, livestock and both human and livestock ailments in the reviewed areas of SNNPR (Giday et al, 2009;Bizuayehu and Assefa, 2017;Andarge et al, 2015;Agisho et al, 2014;Tolossa et al, 2013;Mesfin et al, 2009;Bekalo et al, 2009;Kewessa et al, 2015)…”
Section: Growth Formsmentioning
confidence: 99%
See 2 more Smart Citations